Carotenoids in female and male reproduction. (December 2022) - Pasquariello, Rolando; Anipchenko, Polina; Pennarossa, Georgia; Crociati, Martina; Zerani, Massimo; Brevini, Tiziana AL.; Gandolfi, Fulvio; Maranesi, Margherita
Abstract: Carotenoids are among the best-known pigments in nature, confer color to plants and animals, and are mainly derived from photosynthetic bacteria, fungi, algae, plants. Mammals cannot synthesize carotenoids. Carotenoids' source is only alimentary and after their assumption, they are mainly converted in retinal, retinol and retinoic acid, collectively known also as pro-vitamins and vitamin A, which play an essential role in tissue growth and regulate different aspects of the reproductive functions. However, their mechanisms of action and potential therapeutic effects are still unclear. This review aims to clarify the role of carotenoids in the male and female reproductive functions in species of veterinary interest. In female, carotenoids and their derivatives regulate not only folliculogenesis and oogenesis but also steroidogenesis. Moreover, they improve fertility by decreasing the risk of embryonic mortality. In male, retinol and retinoic acids activate molecular pathways related to spermatogenesis. Deficiencies of these vitamins have been correlated with degeneration of testis parenchyma with consequent absence of the mature sperm. Carotenoids have also been considered anti-antioxidants as they ameliorate the effect of free radicals. The mechanisms of action seem to be exerted by activating Kit and Stra8 pathways in both female and male. In conclusion, carotenoids have potentially beneficial effects for ameliorating ovarian and testes function. Graphical abstract: Image 1 Highlights: Carotenoids are natural pigments with essential role in promoting tissue growth, female, and male reproductive function. Mammals cannot synthetize carotenoids thereby they need to take them from the diet. Carotenoids have a steroidogenic function and act as regulators of folliculogenesis and oogenesis. Retinol and retinoic acid are essential in the development of mature sperm.